Performing colonisation: The manufacture of Black female bodies in tourism research. (September 2017) - Lee, Emma
Highlights: Indigenous epistemologies contribute to tourism decolonisation. Performance theory is uncritically challenged for colonising harms by Establishment men. Black female bodies are performed against and exploited. New methodologies inform new tourism ethics for respectful research. Abstract: This paper is an Indigenous contribution to the epistemic decolonisation of tourism research. To understand how western privilege operates within research I highlight the rise of, what I term here, Establishment men and their use of performance theory and universalisms to both mask and enable harms against Black female bodies. I then introduce an innovative Indigenous methodology in storytelling to consider the depth and richness of contributions away from colonising and linear narratives and towards positive touristic encounters. Finally, I then give an overview of the types and use of ethics to prevent future harms to Black female bodies and establish a pathway towards equity in tourism research.